Portuguese version of Brown, Treviño and Harrison’s Ethical Leadership Scale: Study of its psychometric properties - Vítor Hugo Silva; Ana Patrícia Duarte (Cogent Business & Management, 2022)
AbstractThis paper investigates the psychometric properties of a Portuguese version of the Ethical Leadership Scale across five field studies. The Portuguese ELS (P-ELS) was compared with subscales of a reduced version of the Ethical Leadership at Work questionnaire to check convergent validity (CFI = .95; TLI = .95; RMSEA = .06) and with subscales of organizational justice scale to confirm discriminant validity (all r < .18; p < .05). To assess criterion validity, the extent of the P-ELS’s ability to predict organizational ethical climate was tested (all β coefficients p < .01, except for profit subscale). To check nomological validity, the relationship between ethical leadership and job-related affective well-being mediated by leader-member exchange quality was analyzed (B indirect effect = 0.21; 95% CI = 0.02, 0.41). Results support P-ELS’s unidimensional structure and suggest that it has good construct validity and reliability, therefore, being a useful tool to assess leaders’ ethical behaviors in the workplace.